Diplomatic law : commentary on the Vienna Convention on Diplomatic Relations - Denza, Eileen (O.U.P. OxfordGB, 2004)
Provides a commentary on the 1961 Vienna Convention on Diplomatic Relations. Includes a thorough examination of topical problems in the field, including the abuse of diplomatic immunity, terrorist violence, and hostile demonstrations against embassies.